About Two-Parameter Minimization Method for Solution of Poorly Formulated Problems in respect of Steady Mode Calculation in Complex Electric-Power Systems - A. A. Zalatoi (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper investigates computing characteristics of Newton methods by a parameter and two–parameter method of minimization in respect of poorly formulated algebraic systems of cubic and nonlinear equations of higher order. Some proposals are given to improve computing characteristics of the two-parameter minimization method while solving the problems concerning computation of steady modes in complex electric-power systems.